A New Environmentally Safe Formulation and of Low Cost for Prolonged Release System of Atrazine and Diuron - Cortes, Gracy K. da R.; Vieira, Eunice F. S.; Oliveira, Daniel M.; Cestari, Antonio R.; Arguelho, Maria de Lara P. de M. (Orbital: The Electronic Journal of Chemistry, 2017)
Diuron and atrazine were incorporated in new formulations developed with the purpose to improve herbicides action through release systems, as well as to reduce the environmental toxicity. A low cost formulation (ALG/ESC) was obtained by combining sodium alginate (ALG) with fish scales of the Piau fish (ESC) from the Leporinus elongatus species. From the crosslinking of ALG/ESC with CaCl2, the formulation ALG/ESC-CaCl2 was obtained. For ALG/ESC-CaCl2, the results are successful, showing a prolonged release of 3.5 and 4.5 days for atrazine and diuron, respectively. Based on parameters of an empirical equation used to fit the herbicide release data, it appears that the release systems of diuron and atrazine from ALG/ESC-CaCl2 are by diffusion processes due to anomalous transport, which did not follow Fick’s laws of diffusion. DOI: http://dx.doi.org/10.17807/orbital.v9i3.994